Interactive Electronic Learning Materials in Civic Education: A Technology-Based Approach with Flip PDF Professional - Julian, Fadlizon; Miaz, Yalvema (Universitas Pendidikan Ganesha, 2024)
The development of interactive electronic teaching materials in Civic Education (PPKn) using Flip PDF Professional aims to enhance student engagement and optimize the use of technology in elementary classrooms. This study seeks to develop electronic teaching materials that are valid, practical, and effective in improving students' learning outcomes. The research method used is Research and Development (R&D) with the Four-D Model (Define, Design, Develop, Disseminate). Data collection instruments include validation sheets from subject matter experts, media experts, and language experts; practicality sheets from teachers and students; and effectiveness tests through pre-test and post-test assessments. The validation results indicate that the developed teaching materials are highly valid, with 95% from subject matter experts, 85% from media experts, and 91% from language experts. The practicality of the teaching materials is rated as very high, with 98.33% from teachers and 93.5% from students. The effectiveness test using the N-Gain score shows an average of 0.4455, categorized as moderate improvement, with the pre-test average score of 60.53 increasing to 78.78 in the post-test. These findings demonstrate that the interactive electronic teaching materials developed using Flip PDF Professional are valid, highly practical, and moderately effective for use in Civic Education learning at the elementary school level. Therefore, this teaching material can serve as an innovative solution for teachers to optimize technology-based learning in classrooms.